Friday

April 25, 2014

April 25, 2014

Posted by **Anonymous** on Sunday, May 27, 2012 at 5:35pm.

- Mathh -
**kuai**, Sunday, May 27, 2012 at 6:41pm(x-7)^2

(x-7)(x-7) = x^2-7x-7x+49

= x^2 - 14x + 49

**Related Questions**

Algebra - Solve S=a/(1-r) for r S = a/(1-r) Multiply both sides by 1-r S*(1-r...

Algebra (check my answers) - Please check these answers. Multiply -7(2a2 -4) = -...

Algebra - Can you please check my work? You have helped other students I know. ...

Algebra - Multiply and simplify completely 1. (x-2y)^3 Simplify 2. 2(-3x^3 y^2)^...

Algebra - Simplify 1/r=1/x+1/y Multiply both sides by rxy. Then simplify. I will...

math - Can someone help me with this problem? multiply and simplify 4 1/5 x 10/...

algebra - How do you simplify [2/(x+4)]+2 ----------- [3/(x+4)]+1 I know the ...

Algebra - 1. solve 3-w/6-w = 3/w-6 2. Find the LCM of (8+9z), (64-81z^2), and (8...

algebra - Solve. x/9-1/7=26/63 STEP 1: The LCM is _________ To clear ...

Algebra - I having a hard time with this word problem: A backyard has dimensions...